Religion and attitudes of married individuals toward reproductive health practices in Tacloban City. - Figueroa, Kareen Robediso; Pan, Michael Coyos (Kareen Robediso Figueroa, 2007)
The purpose of this study is to quantitatively explore the attitudes toward Reproductive Health Practices among a sampling of married individuals who are working and affiliated to any of the following religious groups- Roman Catholic, Seventh-day Adventist or Baptist churches respectively. A survey instrument was given to 120 respondents, 40 married individuals (men and women) from each of the religious groups whose mean age was 36.13. Likert scales were used in the composition of the research questionnaire which was pre-tested and revised several times with the aid of experts in validating the items. Their attitude scores were subjected to a 2X3 ANOVA with gender (men and women) and religion (Roman Catholic, Seventh-day Adventist and Baptist) as the independent variables and attitude as the dependent variable. Specifically, the survey sought to find out the knowledge and attitudes of the married individuals towards RH practices; determine the relationship of the respondents respective religious affiliations and their attitudes toward RH practices; know whether the attitudes of the husbands married men RH practices differ from that of the married women; and, relate the attitudes of the married individuals toward RH practices and the interaction of gender and respective religious affiliation. The findings of the study suggested that: the respondents are already knowledgeable about reproductive health and its practices in Family Planning, Abortion and Family Health Care especially of their urban orientation; husbands and wives significantly differed in their attitudes, with its F computed value 7.16, which is greater than the F tabular value 3.92 at alpha 0.05 and degrees of freedom 1, 114 although they both reported favorable views towards RH practices; there was a significant difference in the spouses' religious group in relation to their expressed favorable attitudes towards RH practices with its F computed value 7.03, which is greater than the F tabular value 3.07, at alpha 0.05 and degrees of freedom 2, 114, the significant difference however was only found between Roman Catholics and Seventh-day Adventists, and Roman Catholics and Baptists; and, the interaction of gender and religion in relation to the attitudes of the spouses towards RH, with its F computed value 0.08, lesser than the F tabular value 19.49, at alpha 0.05 and degrees of freedom 114, 2 was found to be not significantly different.
Undergraduate thesis (B.A.S.S. Psychology) -- University of the Philipines, Tacloban.